The COVID-19 Crisis in Romania: A Hypothesis around Penal Populism and Legal Culture - Mercescu, Alexandra (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
In this paper I seek to present a working hypothesis to be eventually developed in a future contribution, namely that the COVID-19 crisis exposed some problematic behaviours evocative of an authoritarian ethos on the part of both public authorities and citizens which suggest that a penal populist attitude might now be part or even embedded in the Romanian legal culture. Specifically, I will organize this contribution as follows: in the first part, I will briefly describe Romania’s reaction (as evidenced both in the official measures taken and the attitude of citizens) to the first wave of the pandemic focusing on the role of penal and military means; I shall qualify this reaction as containing some traces of penal populism. In the second part I shall offer a tentative mapping of the factors that can explain this problematic cultural reaction. Importantly, among these I include the successful fight against corruption with the consequence that what appears to have very much consolidated the rule of law in post-1989 Romania could be shown to have had the unintended and paradoxical effect of undermining the very same ideal.